Cobalt nanoparticle–carbon nanoplate as the solar absorber of a wood aerogel evaporator for continuously efficient desalination. Issue 1 (25th November 2021) - Zhao, Yujuan; You, Dongyu; Yang, Weiting; Yu, Han; Pan, Qinhe; Song, Shuyan
Abstract : Cobalt nanoparticle–carbon nanoplate as the solar absorber of a wood aerogel evaporator for efficient solar steam generation. Abstract : Solar-driven interface water evaporation has shown great potential in seawater desalination. A solar steam generation device with excellent performance requires materials that can efficiently absorb solar energy to achieve photothermal conversion. ZIF-L (a Co-based metal–organic framework) after carbonization has the dual role of carbon nanoplates and cobalt nanoparticles to absorb solar light, exhibiting broad light absorption. Herein, based on carbonized ZIF-L and natural wood, we designed a solar-driven interface water evaporation device, in which ZIF-L after carbonization is used to achieve photothermal conversion, and wood aerogel with high porosity is used as a supporting layer to transport seawater to the evaporation interface and realize self-floating of the device. The prepared evaporator exhibited a high evaporation rate of 1.52 kg m −2 h −1 and an evaporation efficiency of 92.42% under 1 sun illumination, and neither salt accumulation nor a significant decrease in the evaporation rate of the device was observed after continuous operation for 10 evaporation cycles. Additionally, the excellent resistance to salt deposition and automatic salt discharge ability of the evaporator were demonstrated, which can ensure its long-term stable operation. The high-efficiency and stable evaporation performance demonstrate the evaporator's great potential in the practical application of solar energy production of clean water.